Highly stereoselective oxy-Michael additions to alpha,beta-disubstituted nitro olefins: asymmetric synthesis of pseudo-norephedrine derivatives and THP* protected alpha-hydroxy ketones. - Buchanan, D; Dixon, D; Hernandez-Juan, F (2004)
The "naked" anion of (S)-6-methyl delta lactol undergoes efficient oxy-Michael addition to alpha,beta-disubstituted nitro olefins to give the THP* protected Henry products with excellent (95-->98% de) stereocontrol at the beta-position and moderate (up to 3 : 1) stereocontrol at the alpha-position in favour of the syn-diastereoisomer. Nitro group reduction with in situN-Boc protection and THP* removal provides alpha,beta-disubstituted ethanolamine derivatives, while treatment with tetrapropylammonium perruthenate gives THP* protected alpha-hydroxy ketone derivatives in high diasteromeric excess.